2022
DOI: 10.1038/s41598-022-07348-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of esophageal elongation with traction sutures on experimental animal model

Abstract: Esophageal elongation is one of the methods of long gap esophageal atresia treatment. The aim of the study was to determine the best type of traction suture for esophageal lengthening on an animal model. White Pekin Duck’s esophagi were used as a model (fresh-frozen and thawed). The esophagus was cut in half, then both ends were sutured together and extended on a tensiometer. Tested sutures involved simple suture, suture aided by a single or double clip, and suture aided by pledget (10 samples each). Constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…study conducted on an animal model (white Pekin Duck esophagus) showed that when using this technique pledget sutures or a double clip should be used, because the maximal force of traction without tissue disruption and the greatest elongation of esophageal pouches were then achieved [30]. Furthermore, this study showed that gradual tightening of the sliding knot in short periods (intermittent traction) enables tissue adaptation, reduces the risk of ruptures, and should be therefore recommended.…”
Section: External and Internal Traction Suturesmentioning
confidence: 89%
See 1 more Smart Citation
“…study conducted on an animal model (white Pekin Duck esophagus) showed that when using this technique pledget sutures or a double clip should be used, because the maximal force of traction without tissue disruption and the greatest elongation of esophageal pouches were then achieved [30]. Furthermore, this study showed that gradual tightening of the sliding knot in short periods (intermittent traction) enables tissue adaptation, reduces the risk of ruptures, and should be therefore recommended.…”
Section: External and Internal Traction Suturesmentioning
confidence: 89%
“…This is a novel procedure which enables the elongation of the proximal and distal esophagus directly towards each other using sliding knots. Fixation on the thoracic wall is therefore not necessary [11,24,30] . Toczewski's et al…”
Section: External and Internal Traction Suturesmentioning
confidence: 99%
“…This is because they help prevent dislodging of the traction suture, which can be a problem during esophageal elongation. [8] In our patients, enteral feeding was initiated on the 5th day post esophageal anastomosis via the OG tube. At follow-up, all three patients were able to tolerate oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…For the cecum, the representative section was directly adjacent to the aboral part of the ileo-cecal valve; for the colon, it was 20 cm aboral to the ileocecal valve; and for the rectum, it was 10 cm oral to the anus. The excised section was then mounted into a motorized test stand (Sauter THM500N, Kern & Sohn, Balingen, Germany) and subjected to linearly increasing traction forces (Figure 1), which advanced at the standard rate of 10 mm per minute used in such experiments [46][47][48][49]. Traction forces were gauged using a tensiometer (FL100, Kern & Sohn, Balingen, Germany) until the muscular layer was disrupted and the mucosal layer was still visible.…”
Section: Methodsmentioning
confidence: 99%